NEW THINKING IN PUNT MORPHOLOGY - Heel, W. A. van (Research Center for Biology-Indonesian Institute of Sciences, 1971)
This note is to reflect the thoughts, practical work and hopes of two workers in the Netherlands who are angaged in this branch of science, Dr. B.M.Moeliono of the Botanical laboratory at Groningen, and myself at the Rijskherbarium at laiden